2020
DOI: 10.1080/23335432.2020.1728381
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the differences in hip strength, gluteus medius activity, and trunk, pelvis, and lower-limb biomechanics during different functional tasks

Abstract: The purpose of the study was to explore differences in the coronal biomechanics of the trunk, pelvis, hip, and knee joints, and gluteus medius muscle activity (GMed) during walking and step down from two riser heights. Joint kinematics and kinetics from 20 healthy participants were recorded using a 10-camera Qualisys system and force plates, and GMed EMG was recorded using a Delsys Trigno system. Hip abductor strength was measured using a hand-held dynamometer. Pelvic obliquity and lateral trunk bending excurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Nevertheless, a recent study shows that no significant difference was seen in the clinical hip abductor strength measurements with the dynamometer between dominant and non-dominant sides. 19 In the present study mean muscle strength was also assessed between two raters which showed no significant difference in the extent of measurement of strength between two raters for between days and within days measurements. It could be probably because both raters were experienced and qualified physiotherapist.…”
Section: Discussionmentioning
confidence: 50%
“…Nevertheless, a recent study shows that no significant difference was seen in the clinical hip abductor strength measurements with the dynamometer between dominant and non-dominant sides. 19 In the present study mean muscle strength was also assessed between two raters which showed no significant difference in the extent of measurement of strength between two raters for between days and within days measurements. It could be probably because both raters were experienced and qualified physiotherapist.…”
Section: Discussionmentioning
confidence: 50%
“…This result in increased risk of non-contact ACL injury in female soccer players. Sinsurin et al , 2020 [ 27 ] Descriptive laboratory study Level of evidence IV 12 Males and 8 Females (mean age 30.8 ± 7 years) Define differences in the trunk, pelvis,hip, and knee joints, and gluteus medius muscle activity Motion analysis and electromyography Walking and step down from two riser heights. Gluteus Medius has a greater stabilizing role during the step-down tasks Lubahn et al , 2011 [ 28 ] Descriptive laboratory study, Level of evidence III 18 healthy females (mean age 22.3 ± 2.3 years) Examine the muscular activation of the gluteus maximus and gluteus medius Motion analysis and electromyography Double and single leg squat The SLS was most effective exercise for activating the gluteus maximus and gluteus medius.…”
Section: Resultsmentioning
confidence: 99%
“… Motion analysis and electromyography Walking Gluteus medius contributed substantially to the medial compartment compressive force leading to greater dynamic knee valgus Pohl et al 2015 [ 33 ] Descriptive laboratory study Level of Evidence IV 8 healthy, active males (mean age 27 ± 6 years) To experimentally reduce hip-abduction strength and observe the subsequent changes in frontal-plane biomechanics. Superior gluteal nerve block injection and subsequent gait analysis Walking Reduction in hip-abductor strength was not associated with alterations in the frontal-plane gait biomechanics of young, healthy men Sinsurin et al 2019 [ 27 ] Descriptive laboratory study Level of Evidence IV 12 Males and 8 females (mean age 30.9 ± 7 years) explore differences in the coronal biomechanics of the trunk, pelvis,hip, and knee joints, and gluteus medius muscle activity during walking and step down Motion analysis and electromyography Walking and step down Significantly greater knee adduction moments were seen during both step-down tasks comparedto level walking with significantly greater Gluteus medius activity DeJong et al 2019 [ 34 ] Descriptive laboratory study Level of Evidence IV 8 Males and 20 females (mean age 19.6 ± 1.5 years) Determine differences in Ultrasound Imaging gluteal muscle activity during gait. Ultrasound of the gluteus maximus and medius during quiet stance, heel strike, and walking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations